Postcardiotomy extracorporeal membrane oxygenation after elective, urgent, and emergency cardiac operations: Insights from the PELS observational studyCentral MessagePerspective - Silvia Mariani, MD; Alvaro Perazzo, MD, MSc; Maria Elena De Piero, MD; Bas C.T. van Bussel, PhD; Michele Di Mauro, PhD; Dominik Wiedemann, PhD; Sven Lehmann, PhD; Matteo Pozzi, PhD; Antonio Loforte, PhD; Udo Boeken, PhD; Robertas Samalavicius, PhD; Karl Bounader, MD; et al. (JTCVS Open)
Background: Outcomes in cardiac surgery are influenced by surgical priority, with higher mortality in emergency cases. Whether this applies to postcardiotomy venoarterial (VA) extracorporeal membrane oxygenation (ECMO) remains unknown. This study describes characteristics and outcomes of patients undergoing cardiac operations and requiring VA ECMO, stratified by emergency, urgent, or elective operation. Methods: This retrospective multicenter observational study included adults requiring postcardiotomy VA ECMO between 2000 and 2020. Preoperative and procedural characteristics, complications, and survival were compared among the 3 patient groups. The association between emergency surgery and in-hospital survival was investigated through mixed Cox proportional hazard models. Results: The study cohort comprised 1063 patients (52.2%) with elective operations, 445 (21.8%) with urgent operations, and 528 (26%) with emergency operations. Emergency operations included more coronary artery bypass grafting operations (n = 286; 54.2%; P < .001) and aortic procedures (n = 126; 23.9%; P = .001) in patients with more unstable preoperative hemodynamic conditions compared to elective and urgent patients. VA ECMO was initiated more frequently intraoperatively in emergency patients (n = 353; 66.9%; P < .001). Postoperative bleeding (n = 338; 64.3%; P < .001), stroke (n = 79; 15%; P < .001), and right ventricular failure (n = 124; 25.3%) were more frequent after emergency operations. In-hospital mortality was 60.5% in the elective group, 57.8% in the urgent group, 63.4% in the emergency group (P = .191). The crude hazard ratio for in-hospital mortality in emergency surgery was 1.15 (95% confidence interval [CI], 1.01-1.32; P = .039) and dropped to 1.09 (95% CI, 0.93-1.27; P = .295) after adjustment for indicators of preoperative instability. 5-year survival was comparable in 30-day survivors (P = .083). Conclusions: One-quarter of postcardiotomy VA ECMOs are implemented after emergency operations. Despite more complications in emergency cases, in-hospital and 5-year survival are comparable between emergency, urgent, or elective operations.